Peran Pengabdian dan Lingkungan Pesantren bagi Keikhlasan Santri Akhir PP Wali Songo Ngabar - A. Nasih Ahbab; Jauhan Budiwan; Moh. Masduki (Program Studi Pendidikan Guru Madrasah Ibtidaiyah INSURI Ponorogo, 2023)
This study investigates the role of service (pengabdian) and the pesantren social environment in shaping the sincerity character of final-year students at Pondok Pesantren Wali Songo Ngabar. The research is grounded in the increasing need to strengthen spiritual and moral values among students amidst the challenges of modernization, which often shift motivations from sincerity toward more pragmatic orientations. Using a qualitative descriptive approach, this study explores how service activities and social interactions within the pesantren ecosystem contribute to the internalization of sincerity. Data were collected through in-depth interviews, participatory observation, and documentation, involving final-year students, supervising teachers, and pesantren administrators as key sources. The findings reveal that service activities function as a practical medium for cultivating sincerity through routines that train students to work without seeking external rewards, emphasizing responsibility, humility, and devotion. However, the implementation of service is not always optimal, as some students perceive it merely as administrative routines, reducing its spiritual impact. The social environment of the pesantren characterized by religious atmosphere, role modeling from kiai and teachers, and strong peer interactions significantly supports the development of sincerity, although inconsistent supervision and varying levels of student awareness present challenges. Overall, the synergy between structured service activities and a supportive social environment forms an essential framework for fostering sincere character formation among final-year students in the pesantren context.